Reserve Adequacy in Emerging Market Economics. (IMF Working Papers; Working Paper ;, 2001)
This paper analyzes reserve adequacy in emerging market countries. It argues that the old rule of thumb of maintaining reserves equivalent to three months of imports has become obsolete and that, instead, a new benchmark is needed which takes into account the increased importance of capital flows. The paper suggests such a benchmark, consisting of the sum of short-term debt on a residual maturity basis (the external drain) and an allowance for possible capital flight (the internal drain), taking into account differences in country risk and exchange rate regime.